Prevention of Cutaneous Tissue Contracture During Removal of Craniofacial Implant Superstructures for CT and MRI Studies - Maureen Sullivan; Rachael Rossitto; David Casey (eJournal of Oral Maxillofacial Research)
Objectives: Head and neck cancer patients who have lost facial parts following surgical intervention frequently require craniofacial implant retained facial prostheses for restoration. Many craniofacial implant patients require computed tomography and magnetic resonance imaging scans as part of their long-term follow-up care. Consequently removal of implant superstructures and peri-abutment tissue management is required for those studies. The purpose of the present paper was to describe a method for eliminating cranial imaging artifacts in patients with craniofacial implants.Material and Methods: Three patients wearing extraoral implant retained facial prostheses needing either computed tomography or magnetic resonance imaging studies were discussed. Peri-implant soft tissues contracture after removal of percutaneous craniofacial implant abutments during computed tomography and magnetic resonance imaging studies was prevented using a method proposed by authors. The procedure involves temporary removal of the supra-implant components prior to imaging and filling of the tissue openings with polyvinyl siloxane dental impression material.Results: Immediately after filling of the tissue openings with polyvinyl siloxane dental impression material patients were sent for the imaging studies, and were asked to return for removal of the silicone plugs and reconnection of all superstructure hardware after imaging procedures were complete. The silicone plugs were easily removed with a dental explorer. The percutaneous abutments were immediately replaced and screwed into the implants which were at the bone level.Conclusions: Presented herein method eliminates the source of artifacts and prevents contracture of percutaneous tissues upon removal of the implant abutments during imaging.